Stigma Negatif terhadap Mata Pelajaran Matematika dan Dampaknya pada Proses Pembelajaran : Tinjauan Literatur Sistematis - Dede Supriyatna; Dina Nafsa Ashfiya (Yayasan Al-Afif, 2026)
Mathematics is often perceived as a difficult and complicated subject by students at various levels of education. This negative stigma has an impact on low motivation, self-confidence and learning outcomes. This research aims to examine students' stigma towards learning mathematics through the Systematic Literature Review (SLR) method. The articles studied come from national journals that are relevant to the topic of mathematics perception and learning. The results of the study show that mathematics stigma is influenced by less varied learning methods, unpleasant learning experiences, as well as students' psychological factors. Therefore, more contextual and innovative learning strategies are needed to reduce the negative stigma towards mathematics.